Toxicity Evaluation of the Naphthalen-2-yl 3,5-Dinitrobenzoate: A Drug Candidate for Alzheimer Disease - Anwar, Fareeha; Saleem, Uzma; Rehman, Atta-Ur; Ahmad, Bashir; Froeyen, Matheus; Mirza, Muhammad Usman; Kee, Lee Yean; Abdullah, Iskandar; Ahmad, Sarfraz (Frontiers in Pharmacology, 2021)
The presented study was designed to probe the toxicity potential of newly identified compound naphthalen-2-yl 3,5-dinitrobenzoate (SF1), having excellent in vivo anti-Alzheimer activity (via AChE inhibition) in our previous work. Acute, subacute toxicity and teratogenicity studies were performed as per OECD 425, 407 and 414 test guidelines, respectively. An oral dose of 2000 mg/kg to rats for acute toxicity. Furthermore, 5, 10, 20 and 40 mg/kg doses were administered once daily for 28 days in subacute toxicity study. Teratogenicity study was performed with 40 mg/kg due to its excellent anti-Alzheimer results at this dose. SF1 induced a significant rise in ALP, bilirubin, WBC, and lymphocyte levels with a decrease in platelet count. Furthermore, the reduction in urea, uric acid, and AST levels and an increase in total protein levels were measured in subacute toxicity. SF1 increased spermatogenesis at 5 and 10 mg/kg doses. Teratogenicity study depicted no resorptions, early abortions, cleft palate, spina bifida and any skeletal abnormalities in the fetuses. Oxidative stress markers (SOD, CAT, and GSH) were increased in all the experiment, whereas the effect on MDA levels was variable. Histopathology further corroborated these results with no change in the architectures of selected organs. Consequently, a 2000 mg/kg dose of SF1 tends to induce minor liver dysfunction along with immunomodulation, and it is well below its LD50. Moreover, it can be safely used in pregnancy owing to its no detectible teratogenicity.